2011
DOI: 10.1111/j.1540-6210.2011.02482.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey Research in Public Administration: Assessing Mainstream Journals with a Total Survey Error Framework

Abstract: Survey research is a common tool for assessing public opinions, perceptions, attitudes, and behaviors for analyses in many social science disciplines. Yet there is little knowledge regarding how specifi c elements of survey research methodology are applied in practice in public administration. Th is article examines fi ve mainstream public administration journals over an eight-year period regarding current methodological practice, organized around the total survey error framework. Th e fi ndings show that surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 55 publications
0
90
1
1
Order By: Relevance
“…On the other hand, it is worth mentioning that these results are completely in line with the results of other CAs in the field. Namely, methodological weaknesses in PA research were identified in CAs conducted by Perry & Kraemer (1986), Lee et al (2009), andWalker et al (2014).…”
Section: Discussion and Recommendations: What Has Been Done And How Tmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it is worth mentioning that these results are completely in line with the results of other CAs in the field. Namely, methodological weaknesses in PA research were identified in CAs conducted by Perry & Kraemer (1986), Lee et al (2009), andWalker et al (2014).…”
Section: Discussion and Recommendations: What Has Been Done And How Tmentioning
confidence: 99%
“…In the field of PA, CA was first conducted among doctoral dissertations in the field (Lee et al, 2009), but later often extended to research papers. However, previous CAs in this field were mainly focused on US-based PA research, while there has never been a CA conducted in the field of Slovenian PA research.…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…So, the survey represents approximately the whole population of officially known Dutch PPP projects up to 2014. By including almost the entire population in our study, we avoid many of the issues with regard to representation as described in the total survey error framework (see, for example, Groves andLyberg 2010 or Lee, Benoit-Bryan, andJohnson 2012). Coverage or sampling errors, which arise in the process of selecting a sample from a target population, are therefore most likely not present in our study.…”
Section: Survey and Variablesmentioning
confidence: 99%